1989
DOI: 10.1152/jappl.1989.66.4.1685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a thromboxane receptor antagonist on PGD2- and allergen-induced bronchoconstriction

Abstract: In this study we investigated the effect of the selective and potent thromboxane A2 (TxA2) receptor antagonist GR32191 on smooth muscle contraction induced by the TxA2 analogue U46619, prostaglandin (PG) D2, PGF2 alpha, and methacholine (MCh) in guinea pig airways in vitro and the airways response provoked by inhaled PGD2 and MCh in asthmatic subjects in vivo. GR32191 antagonized competitively the contractile responses of all three prostanoids to a similar degree but had no effect on MCh-induced contractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
63
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 0 publications
11
63
1
Order By: Relevance
“…In contrast, Chinese hamster ovary cells transfected with the recombinant mouse DP receptor, PGD 2 and BW245C competitively inhibited binding of radiolabeled PGD 2 with K i values of 21 nM and 250 nM, respectively. 23 This data is consistent with the differences observed for DP receptor binding of BW245C in mice versus humans. 2 We have previously demonstrated that PGE 1 causes cAMP levels to increase to 750 -1000 pmol=mg protein in human cavernosal smooth muscle cells through either the EP2 and=or EP4 receptors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, Chinese hamster ovary cells transfected with the recombinant mouse DP receptor, PGD 2 and BW245C competitively inhibited binding of radiolabeled PGD 2 with K i values of 21 nM and 250 nM, respectively. 23 This data is consistent with the differences observed for DP receptor binding of BW245C in mice versus humans. 2 We have previously demonstrated that PGE 1 causes cAMP levels to increase to 750 -1000 pmol=mg protein in human cavernosal smooth muscle cells through either the EP2 and=or EP4 receptors.…”
Section: Discussionsupporting
confidence: 89%
“…A similar phenomenon has been reported in nonvascular smooth muscle in the lung, where PGD 2 plays a role in bronchoconstriction via TP receptors. 23 The pharmacological results are consistent with RT-PCR data demonstrating DP receptor mRNA in both corpus cavernosum smooth muscle biopsy specimens and cultured smooth muscle cells. The tissue distribution of the rat DP receptor has been characterized and found predominantly in the brain in the leptomeninges and peripherally in the eye and in the oviduct.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At least 10 receptors are involved in prostaglandin signalling, and many prostaglandins can interact with multiple receptors. In this regard, PGD 2 has been reported to interact with both the DP receptor and the TP receptor [26]. The DP receptor is believed to activate adenylyl cyclase and lead to an increase in cAMP [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the bronchoconstrictory effect exerted by PGD 2 is believed to be mediated through the TP receptor [26]. HIRAI et al [28], recently demonstrated that PGD 2 could induce chemotaxis of T-helper 2 cells, eosinophils and basophils by way of the seven-transmembrane receptor CRTH2.…”
Section: Discussionmentioning
confidence: 99%